Potensi dan Strategi Pengembangan Peternakan di Kabupaten Mesuji - Maksum, Maksum; Herdiansah, Riko; Wicaksana, Kunaifi (Fakultas Peternakan Universitas Tulang Bawang, 2023)
The purpose of this study is to determine the potential and strategies for the livestock sector that can be developed in Mesuji District. Material in the form of primary and secondary data. Primary data were obtained from respondents who understood the condition of the livestock sub-sector and secondary data were obtained from data from the Mesuji Regency Central Bureau of Statistics (BPS) and data from the Mesuji Regency Agriculture Service. The data analysis used is Location Quotient (LQ) analysis and SWOT analysis. The results of this study include goat farming which has the highest potential among other livestock commodities to be developed in Mesuji Regency. The strategy that can be developed is a defensive strategy because the weaknesses and threats in the development of goat farms in Mesuji Regency are high. The conclusion in this study is to increase the knowledge of breeders in caring for goats and improve facilities and infrastructure so that goat farming businesses can grow and develop.